Early Quaternary Tectonic Transformation of the Helan Shan: Constraints Due To Quantitative Geomorphology - Li, Yige; Zheng, Wenjun; Yang, Jingjun; Zhang, Dongli; Zhou, Haoyu; Liu, Ting (Frontiers in Earth Science, 2022)
The Helan Shan is located on the front edge of the expanding Tibetan Plateau. However, how the topography here responds to this propagation and its precise time constraints remains unknown. Based on the response process of fluvial landforms and tectonic evolution, we conducted a quantitative landform analysis of the Helan Shan region. Here, the spatial distribution features of various geomorphic indices were coupled, demonstrating that the mountain is tilting toward the west and north. The steeper downstream and gentle upper reaches indicate that the fluvial landforms have experienced an accelerated incision event, which can be attributed to the tectonic activity along the East Helan Shan Fault. Furthermore, the response time of the tectonic knickpoints ranges from 0.1¬–1.4 Ma based on the paleochannel reconstruction method. Combined with previous studies on low temperature thermochronology and active tectonics, we propose a tectonic transformation model where the Helan Shan shifted the tilting model from the southwest to the northwest, as induced by the northeast expansion of the Tibetan Plateau from 0.1–1.4 Ma.